Discharge Readiness and Associated Factors Among Patients with Coronary Heart Disease After Stent Implantation: A Cross-Sectional Single Center Study - Shu, Pan; Xuan, Lijuan; Jiang, Xiaolian (Patient preference and adherence, 2024)
The aim of this study is to describe the readiness of hospital discharge of patients with coronary heart disease (CHD) who have undergone coronary stent implantation and explore its influencing factors. This is a cross sectional single center study. Convenient sampling was used to select patients who underwent coronary stent implantation in the Cardiovascular Department of a tertiary hospital in Chengdu from October 2021 to April 2022 as the research subjects. Data were collected using the General Information Questionnaire, which included domains such as uncertainty in illness, the quality of discharge teaching, perceived social support, and health locus of control. The Readiness for Hospital Discharge Scale (RHDS) was used to assess readiness for hospital discharge. Multiple regression adjusted for relevant confounders was used to determine the associations. A total of 276 questionnaires were distributed, and 263 valid questionnaires were collected. The average item score of RHDS is 7.66 ± 1.13. Multiple regression analysis indicated that the influential factors of RHDS of patients who underwent coronary stent implantation included: deliver skill (β = 0.43), marital status (β = 0.12), living alone (β = -0.14), inconsistency (β = -0.22) and household income per capita (β = -0.12) (all <0.05). The RHDS score of patients with CHD after coronary stent implantation were at a moderate level. Discharge readiness was significantly associated with delivery skill, marital status, living alone, inconsistency of information, and household income per capita. The present study highlights the need for improved educational interventions and tailored discharge planning.